SIMULASI KEKUATAN PANEL LAPIS STRUKTUR SARANG LEBAH KOMPOSIT POLIMER DIPERKUAT SERAT DAUN NANAS - Ellyawan Setyo Arbintarso; Taufiq Hidayat; Yuli Purwanto (IST AKPRIND Yogyakarta, 2018)
Honeycomb construction is a mimicry construction of a nest of bees/wasps form. The original form of honeycomb is hexagonal but in the development of the manufacturing process is transformed into other forms, e.g., quadrilateral, pentagonal, and polygonal. Honeycomb construction is widely used as a wall or panel because of its lightweight, lightweight obtained from the influence of the cavity due to the connection of each facet. In general, this honeycomb construction is not used for construction that receives either axial or radial loads. The axial load testing, especially using a three-point bending test was used in this research. The pineapple fiber-reinforced polymer composite is proven to have good damping ability which is expected to be suitable for alternative materials in the manufacture of the honeycomb structure. The honeycomb structure is hexagonal, which will be the core of a construction. The construction will be axially loaded which will be represented by a three-point bending test. In addition to direct testing, simulation of loading using Autodesk Inventor software will be compared and analyzed further. The mechanical properties, especially the bending stress for construction with a honeycomb core, are particularly useful in the design of an impacted construction, bent, and lightweight. The result of the simulation shows the difference with the test result caused by several factors, i.e., 1. The thickness of the honeycomb was not uniform, 2. There is a defect (air cavity) in the specimen, 3. Simulation has difficulties in determining the load and support of the nonsolid structure